PRIVASI DATA DAN TRANSPARANSI: TANTANGAN ETIS DALAM PENERAPAN ARTIFICIAL INTELLIGENCE (AI) DI BIDANG AKUNTANSI - Uswatun Hasanah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tjut NYak Dhien, 2024)
This study aims to examine the ethical challenges and implications of using Artificial Intelligence (AI) in accounting practices, with a particular focus on issues related to data privacy, decision-making transparency, and algorithmic bias, as well as the potential disruption of traditional accounting roles by AI. The methodology employed is a systematic literature review of various academic sources and relevant publications that discuss the ethical aspects of AI implementation in accounting. The results of the study indicate that while AI offers several benefits, such as increased efficiency and accuracy, it also presents significant ethical challenges. These challenges include the risk of data privacy breaches, a lack of transparency in AI-supported decision-making processes, and potential biases in algorithms that could lead to unfair practices in accounting. Moreover, the traditional role of accountants is increasingly threatened by AI-driven automation, which may fundamentally alter the dynamics of work in the accounting field. In conclusion, although AI holds great potential for enhancing accounting practices, it is crucial for professionals and policymakers to address and mitigate the emerging ethical challenges. This approach ensures that AI integration into accounting is conducted responsibly and in alignment with professional ethical principles.